Endoscopic port access surgery for isolated atrioventricular valve endocarditis. (2nd April 2018) - van der Merwe, Johan; Casselman, Filip; Stockman, Bernard; Roubelakis, Apostolos; Vermeulen, Yvette; Degrieck, Ivan; Van Praet, Frank
Abstract: OBJECTIVES: Our goal was to report the clinical and echocardiographic outcomes of endoscopic port access surgery for isolated active and convalescent atrioventricular valve endocarditis (AVVE). METHODS: Our current surgical team performed endoscopic port access surgery in 66 consecutive patients with isolated AVVE (mean age, 65.5 ± 12.7 years, 37.9% women, mean EuroSCORE II 31.2 ± 24.9%, 45.5% prosthetic AVVE, Staphylococcus aureus 22.2%), between 1 May 2004 and 31 July 2015. Isolated mitral valve endocarditis was present in 53 (80.4%) patients, including 11 (16.7%) with periannular abscesses. RESULTS: Procedures performed included mitral valve repair ( n  = 15, 22.7%) and left ventricular septal myomectomy ( n  = 1, 1.5%). Reasons for sternotomy conversion ( n  = 6, 9.1%) included lung adhesions ( n  = 3, 4.5%). The mean cardiopulmonary bypass and ischaemic times were 167.2 ±48.7 and 112.6 ± 33.3 min, respectively. In-hospital morbidities included revision for bleeding ( n  = 6, 9.1%). The 30-day survival rate was 87.9%. Causes of in-hospital deaths ( n  = 12) included low cardiac output syndrome ( n  = 3, 4.5%). Age, critical preoperative status and EuroSCORE II score predicted deaths individually at the 5% level of significance. The Kaplan–Meier analyses (mean 63.2 ± 42.5 months) for survival and freedom from AVVE reintervention at 10 years were 69.4% and 98.4%, respectively. Of the mid-term survivors ( n  = 50, 93.9% complete), 94.0% ( n  = 47) classified as New York Heart Association (NYHA) II or less with no mitral valve regurgitation greater than Grade I. CONCLUSIONS: Complex atrioventricular valve surgery in the context of AVVE can be endoscopically performed in experienced centres and should not deter surgeons from offering patients with AVVE the potential benefits of minimally invasive cardiac surgery.